Strategi Guru MI dalam Membentuk Etika Digital pada Peserta Didik di Era Media Sosial - Ulfa Nurfitri Aprilia; Fitri Hidayati Lestari; Linda Ayu Sahara; Suttrisno Suttrisno (Lembaga Pengembangan Kinerja Dosen, 2025)
The abstract of this research aims to explore the strategies implemented by Madrasah Ibtidaiyah (MI) teachers in forming digital ethics in students in the era of social media. With the increasing use of social media among children and teenagers, digital ethics education has become crucial to ensure that students can use technology wisely and responsibly. This research uses a qualitative approach with data collection methods through in-depth interviews, direct observation, and analysis of curriculum documents. The research results show that MI teachers integrate character values ​​into digital ethics learning, utilize group discussions, and use technology as a learning tool. Apart from that, collaboration with parents has also proven important in supporting digital ethics education. Despite challenges such as limited technological infrastructure and differences in student backgrounds, suggestions for increasing the effectiveness of digital ethics education include increasing teacher capacity, systematic curriculum development, and parental involvement. Thus, this research provides insight into the importance of digital ethics education in MI and the strategies that can be implemented to form an intelligent and characterful young generation in the era of social media. without any references or formulas.